Design and Optimization of Orodispersible Mucoadhesive Films of Nitrazepam Using Quality by Design (QbD) for Enhanced Neurotherapeutic Onset - Wairagade, Sonali; Patnaik, Soumya Stuti; Mart, E. Joel; Rathore, Amit; Chundawat, Rituraj Singh; F Mehta, Farhad; Chatla, Supriya; Suresh, R. (Journal of Neonatal Surgery, 2025)
This study presents the design and optimization of orodispersible mucoadhesive films (ODFs) of Nitrazepam utilizing a Quality by Design (QbD) approach to achieve rapid neurotherapeutic onset and improved patient compliance. Nitrazepam, a BCS Class II benzodiazepine with low aqueous solubility and extensive first-pass metabolism, poses challenges for conventional oral delivery systems, especially in acute neurological conditions requiring rapid pharmacological intervention. To address this, solvent casting was employed to formulate polymeric films using Hydroxypropyl Methylcellulose (HPMC E5), propylene glycol, sodium starch glycolate, and aspartame. A Central Composite Design (CCD) was applied using Design Expert software to optimize critical formulation parameters. Films were evaluated for disintegration time, folding endurance, surface pH, drug content, in-vitro release, and stability under accelerated conditions. The optimized formulation exhibited rapid disintegration (25.1 ± 1.53 s), high folding endurance (205 ± 5), near-neutral pH (7.07 ± 0.19), and >97% drug release within 10 minutes. Kinetic analysis confirmed non-Fickian (anomalous) transport governed by both diffusion and polymer erosion mechanisms. FTIR confirmed drug-excipient compatibility, while stability studies validated the formulation's physical integrity and potency over 30 days. The QbD-based methodology enabled rational design with predictive control, ensuring batch robustness and scalability. Overall, the developed Nitrazepam ODF offers a clinically viable alternative to conventional tablets, particularly in pediatric, geriatric, and emergency neuropsychiatric settings, promising enhanced bioavailability, faster therapeutic onset, and superior patient-centric performance.